Effects of Social Skills on Early Childhood Independence - Rusmayadi Rusmayadi; Herman Herman; Herman (Journal of Educational Science and Technology (EST), 2019)
The purpose of the study was to determine the effect of social skills on children's independence. The research method is a survey that explains the causal relationship between path analysis and a quantitative approach. In the study found that there is a significant relationship between Social Skills with Independence. The closeness of the relationship between interpersonal and Independence is reinforced by the results of testing the hypothesis that there is a positive direct effect of Interpersonal Intelligence on Independence. The results showed there was a direct influence of Social Skills on the Independence of kindergarten children. Hypothesis testing results indicate the research hypothesis is accepted. Thus it can be interpreted that there is a significant direct effect of Social Skills on the Independence of Kindergarten children.